BOLAJAQ TEXNOLOGIYA OQÍTÍWShÍLARÍNÍŃ KÁSIPLIK KOMPETENTLIGIN RAWAJLANDÍRÍW - Abdieva, S.P. (SCIENCE and SOCIETY, 2025)
The article presents the professional competencies of future technology educators and the main ways and effective methods of developing them. It also analyzes the level of professional training required from the teacher of technology in the modern educational process, innovative approaches.